Characterization of texture and microstructure of instant analog rice based on soybean–seaweed formulation - Lola Ayu Istifiani; Rahma Micho Widyanto; Aprinia Dian Nurhayati; Irma Sarita Rahmawati; Dita Oktavia Maharani (AcTion: Aceh Nutrition Journal, 2026)
The prevalence of type 2 Diabetes Mellitus (T2DM) continues to rise, and the consumption of high-glycemic index white rice contributes to postprandial hyperglycemia. Alternatives with a low glycemic index that are practical and nutritionally rich remain limited. This study aimed to evaluate the texture and microstructure of instant analog rice based on soybean and seaweed to support T2DM risk management. A completely randomized design with three replicates per treatment was used. The formulations included soybean: seaweed ratios of 40%:60% (P2), 50%:50% (P3), and 60%:40% (P4), along with 100% instant rice as the control (P1). Texture was analyzed using Texture Profile Analysis, and microstructure was observed with a Scanning Electron Microscope (magnification 2000×, 15 kV). Results, significant differences were observed in hardness (P3: 5.21 N), cohesiveness (P2: 0.62), and resilience (P2: 0.41). SEM images showed more porous granules in P2–P4, which correlated with lower hardness and faster rehydration. Formulation P4 (60% soybean:40% seaweed) exhibited moderate hardness (4.87 N), acceptable cohesiveness, and a porous microstructure, supporting its nutritional value and functional properties. In Conclusion, instant analog rice P4 has the potential to serve as a functional food that is practical for T2DM prevention and management, providing a suitable texture and nutritional benefits that support metabolic health.